The Urgency of Pregnancy Risk Factors Booklet - Indri Astuti Purwanti; Nuke Devi Indrawati; Arief Tajally Adhiatma (Universitas Muhammadiyah Semarang, 2017)
Maternal mortality cases in Semarang city were still high in 2015. Among all district in Semarang city, work area of Puskesmas Bandarharjo had the most maternal mortality cases. All pregnant women there had not beenrealized their risk pregnancy factors. Hence, they need health education about pregnancy risk factors to changetheir mindset. The right media in health education is booklet because it is written, can be colorful, can containpictures to explain the information and not limited by pages. It also can influence behavior intention of thepregnant woman, her husband, her parents, her parents in law and other people who read the book to detect earlypregnancy risk factors.Keywords: maternal mortality, pregnancy risk factors, media health education.